The Action of Bioactive Compounds on Human Health or Disease (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Bioactive compounds are being studied to better understand their effects on health and disease. These compounds are found in several foods, such as beverages (wine, cedar, and juices), vegetable oils, spices (curcuma, pepper, etc.), teas, and infusions. In in vitro and in vivo studies, some of these compounds have already shown several potentially beneficial effects on human health and in the prevention of disease. Plant bioactive compounds are of great interest in these areas due to the range of compound varieties and actions, such as thermogenesis, inflammation, metabolism, and endocrine factors. More research is needed to explore their use in improving physical performance; the aging process; and preventing or helping treat diseases such as obesity, CVD, diabetes mellitus tumors, and inflammatory processes in general.